2020
DOI: 10.3389/fped.2020.00469
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Symptoms in Preschool Children With Autism Spectrum Disorder: A Two-Center Comparative Study in Chongqing and Hainan Province, China

Abstract: The study aimed to compare the nutritional status and symptoms of preschool children with autism spectrum disorder (ASD) from two regions of China, and to analyze the association between nutritional status and symptoms of ASD. Methods: In this cross-sectional study, 738 ASD children and 302 typically developing children (TD) were recruited from Chongqing and Hainan of China. Symptoms of ASD children were evaluated with the Autism Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and Childhood Autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
(69 reference statements)
2
30
1
Order By: Relevance
“…Feeding problems, such as being a picky eater, lack of food variety, and resistance to new foods are more prevalent than in typically developing children. It is reported that children with ASD often prefer energy-dense foods such as meat, sugar-sweetened beverages, and snacks, and reject vegetables and fruits ( 34 , 35 ). In our study, children with ASD exhibited more picky eating, especially resistance to vegetables, as compared with TD children.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding problems, such as being a picky eater, lack of food variety, and resistance to new foods are more prevalent than in typically developing children. It is reported that children with ASD often prefer energy-dense foods such as meat, sugar-sweetened beverages, and snacks, and reject vegetables and fruits ( 34 , 35 ). In our study, children with ASD exhibited more picky eating, especially resistance to vegetables, as compared with TD children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thirteen of the remaining records were excluded through full-text reading (7 records with overlapping data, 1 record with insufficient data, 2 reviews, and 3 abstracts). The study conducted by Zhu et al reported the results in two different regions ( 27 ). We treated the report by Zhu et al as two different studies: Zhu 2020 (1) and Zhu 2020 (2).…”
Section: Resultsmentioning
confidence: 99%
“…We treated the report by Zhu et al as two different studies: Zhu 2020 (1) and Zhu 2020 (2). Finally, five records (6 studies) with 1,451 unique participants were included in our meta-analysis to evaluate the association between the concentration of vitamin A and ASD (27)(28)(29)(30)(31). The flow diagram is shown in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Multiple studies have shown that individuals with ASD have lower levels of VA compared to typically developing (TD) children or family members [17][18][19][20][21]. An assessment of nutritional intake for 3 consecutive days in 367 ASD children aged 2 to 11 years in the United States (National Health and Nutrition Examination Survey data and matched subsets based on age, sex, family income, and race/ethnicity (N = 252 analyzed food records)), using a developing country information system, found that ASD children aged 4 to 8 years had significantly lower VA intake than controls [22].…”
Section: Vitamin a Levels In Asd Patientsmentioning
confidence: 99%
“…Previous studies were limited to the nutritional status of ASD children in a single region, but a recent study recruited 738 children with ASD and 302 TD children from Chongqing and Hainan (China) to compare their nutritional status and symptoms and analyze their response to nutritional levels and ASD symptoms [ 21 ]. They used the ABC, SRS, and CARS to evaluate the symptoms of ASD children and the GDS to assess neurodevelopment in ASD children.…”
Section: Vitamin a Levels In Asd Patientsmentioning
confidence: 99%